2015
DOI: 10.1149/2.0131506jss
|View full text |Cite
|
Sign up to set email alerts
|

A Neutral Beam Process for Controlling Surface Defect Generation and Chemical Reactions at the Atomic Layer

Abstract: Advances in plasma process technology have contributed directly to advances in the miniaturization and integration of semiconductor devices. However, in semiconductor devices that encroach on the nanoscale domain, defects or damage can be caused by charged particles and ultraviolet rays emitted from the plasma, severely impairing the characteristics of nano-devices that have a larger surface than bulk areas. It is therefore essential to develop a method for suppressing or controlling charge accumulation and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Interest in ALE has increased considerably in the last few years [60,61]. Although some of the recent work can more accurately be termed nano-scale layer-by-layer etching, it is undeniable that the microelectronics industry is seeking etch solutions that remove materials with atomic precision, doing it with high selectivity between materials, and leaving the unetched material atomically pristine.…”
Section: Atomic Layer Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in ALE has increased considerably in the last few years [60,61]. Although some of the recent work can more accurately be termed nano-scale layer-by-layer etching, it is undeniable that the microelectronics industry is seeking etch solutions that remove materials with atomic precision, doing it with high selectivity between materials, and leaving the unetched material atomically pristine.…”
Section: Atomic Layer Processingmentioning
confidence: 99%
“…These attributes enable precise nano-processing, which suppresses the formation of defects at the atomic layer level and controls the surface chemical reactions with high precision. Atomic layer defect-free and roughness-free Si (or Ge) channel etching for sub-22 nm Fin-FETs (figure 11) [61,62], ultra-thin gate dielectric film formation for sub-22 nm Fin-FETs, transition metal oxidation for ReRAM, atomic layer super-low dielectric film deposition for sub-22 nm FETs, atomic layer damage-free etching of magnetic materials [61] and low-damage surface modification of carbon materials (including nanotubes, grapheme, and organic molecules) for future nano-devices using neutral beam processing have been demonstrated.…”
Section: Atomic Layer Processingmentioning
confidence: 99%
“…Samukawa and coworkers developed a novel defect‐free etching technique for semiconductor materials, that is, the neutral beam etching (NBE) technique . The neutral beam suppresses the incidence of charged particles and UV photon radiation onto the substrate, and is able to expose the substrate only to energy‐controlled neutral beam.…”
Section: Introductionmentioning
confidence: 99%
“…Realistically, numerous fabrication QD processes have been reported, [3][4][5][6][7][8][9][10] yet the experimental results only reveal the possibility of fabricating larger QD (diameter or thickness greater than 10 nm). By combining a self-assembled ferritin biotemplate, we have advanced a topdown nanofabrication methodology, damage-free neutral beam etching 11,12) (NBE), which has been applied to fabricate high-quality discoid QDs of sub-10-nm size, [13][14][15][16] which will benefit the investigation of minute-sized QDs. Recent research on optical applications of QDs [17][18][19][20][21] has been reported.…”
Section: Introductionmentioning
confidence: 99%